Appendix to ``Regularity of Villadsen algebras’’: The failure of the Corona Factorization Property for the Villadsen algebra V_∞ - Bosa, Joan; Christensen, Martin S. (MATHEMATICA SCANDINAVICA, 2018)
In this appendix to M. S. Christensen, “Regularity of Villadsen algebras and characters on their central sequence algebras”, Math. Scand. ?? (????), ???–???, we prove that the Villadsen algebra V _∞ does not satisfy the Corona Factorization Property (CFP).